Shifting Nursing Care Models as a Solution for the Increasing Demand on Intensive Care Unit Beds During a Pandemic: A Case Study. Issue 2 (March 2022) - Geltmeyer, Klara; Dehennin, Laurence; Vanacker, Tom; Goedertier, Hilde; Verhaeghe, Rik; Benoit, Dominique; Malfait, Simon
Abstract : Aim: An option appraisal of different nursing care delivery models was presented, which were made in between the first and second COVID-19 waves. The authors wanted to inform colleagues on involving nursing care delivery models in the problem-solving process during a pandemic. Local Problem: In the pre–COVID-19 hospital practice, the nursing care delivery model of primary nursing was applied in the intensive care unit (ICU). However, during the COVID-19 pandemic, this situation could not be upheld because of the increased need for ICU beds and the shortages of available ICU nurses. Methods: This study used the literature of an ongoing systematic review on nursing care delivery models and expert meetings between the authors and nursing staff. Results: One standard nursing care delivery model and 3 alternative nursing care delivery models were discussed and compared in this case study. Theoretically, a modular system of team nursing seemed the better model to use during a pandemic. This model leads to an equal distribution of expertise and social distancing between experts. Compared with the other models, a strategic reserve can be created. Conclusion: This case study should be primarily considered as an example on how rethinking and reorganizing the nursing care delivery model could contribute to an enlarged, qualitative capacity, which needs to be organized in a short time span.